Person and deixis in Heiltsuk pronouns. (December 2019) - Bjorkman, Bronwyn M.; Cowper, Elizabeth; Hall, Daniel Currie; Peters, Andrew
Abstract: Harbour (2016) argues for a parsimonious universal set of features for grammatical person distinctions, and suggests (ch. 7) that the same features may also form the basis for systems of deixis. We apply this proposal to an analysis of Heiltsuk, a Wakashan language with a particularly rich set of person-based deictic contrasts (Rath 1981). Heiltsuk demonstratives and third-person pronominal enclitics distinguish proximal-to-speaker, proximal-to-addressee, and distal (in addition to an orthogonal visibility contrast). There are no forms marking proximity to third persons (e.g., 'near them') or identifying the location of discourse participants (e.g., 'you near me' vs. 'you over there'), nor does the deictic system make use of the clusivity contrast that appears in the pronoun paradigm (e.g., 'this near you and me' vs. 'this near me and others'). We account for the pattern by implementing Harbour's spatial element χ as a function that yields proximity to its first- or second-person argument. Résumé: Harbour (2016) propose un ensemble universel et parcimonieux de traits universels pour rendre compte des distinctions grammaticales de personne, et suggère (ch. 7) que ces mêmes traits peuvent également servir de base aux systèmes de deixis. Nous appliquons cette approche à une analyse de heiltsuk, une langue wakashan avec un système particulièrement riche de contrastes déictiques basés sur la personne (Rath 1981). Les démonstratifs de heiltsuk, ainsi que les enclitiques pronominaux à la troisième personne, distinguent entre le proximal au locuteur, le proximal à l'écouteur, et le distal (en plus d'un contraste orthogonal de visibilité). Il n'y a pas de formes qui marquent la proximité à une troisième personne (p. ex. 'près d'eux') ni qui situent les participants au discours (p. ex. 'vous près de moi' vs 'vous à distance'). Le système démonstratif n'utilise pas non plus le contraste de clusivité qui figure dans le paradigme pronominal (par exemple, 'celui près de toi et de moi' vs 'celui près de moi et d'autres'). Nous expliquons ce système en modifiant l'élément spatial χ de Harbour (2016), en une fonction qui retourne une relation de proximité par rapport à son argument de première ou de deuxième personne.